2014
DOI: 10.1016/j.biopsych.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Speech Disturbs Face Scanning in 6-Month-Old Infants Who Develop Autism Spectrum Disorder

Abstract: Background From birth, infants show a preference for the faces, gaze, and voices of others. In individuals with autism spectrum disorders (ASDs) these biases appear to be disturbed. The source of these disturbances is not well-understood, but recent efforts have shown that the spontaneous deployment of attention to social targets may be atypical as early as 6 months of age. The nature of this atypical behavior and the conditions under which it arises are currently unknown. Methods We used eye-tracking to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
135
4
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(164 citation statements)
references
References 85 publications
11
135
4
8
Order By: Relevance
“…To our knowledge, only a few studies quantitatively compare attention to stimuli of different social complexity in autism spectrum disorders in real-life settings (e.g., by analyzing retrospective home videos). Note that our results agree with the recent eye-tracking studies conducted in semi-naturalistic settings by Chawarska et al [54] and Shic et al [55]. Both studies reported that children with ASD looked proportionally less time at an actor's face, when the actor was speaking, than TD children and children with developmental delays.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To our knowledge, only a few studies quantitatively compare attention to stimuli of different social complexity in autism spectrum disorders in real-life settings (e.g., by analyzing retrospective home videos). Note that our results agree with the recent eye-tracking studies conducted in semi-naturalistic settings by Chawarska et al [54] and Shic et al [55]. Both studies reported that children with ASD looked proportionally less time at an actor's face, when the actor was speaking, than TD children and children with developmental delays.…”
Section: Discussionsupporting
confidence: 93%
“…The authors hypothesize that the differences across groups could be explained by the degree of social complexity involved in the scenes, e.g., in the presence of social cues such as eye contact and speech. In another recent eye-tracking study, Shic et al [55] find that 6-month-old children, who were later diagnosed with ASD, looked proportionally less time at the inner features of the face when an actor was speaking, compared to all other groups.…”
Section: Introductionmentioning
confidence: 96%
“…Cette méthode non invasive, ne nécessitant pas de porter un équipement sur la tête ou d'autres dispositifs importuns, permet aux chercheurs de mesurer comment l'observateur, quel que soit son âge, distribue son regard et peut aussi contribuer à répondre à un large éventail de questions scientifiques [20]. En particulier, les personnes avec TSA passent généralement un pourcentage de temps plus faible à regarder les autres individus [21,23] et elles se centrent moins sur les caractéristiques centrales du visage au profit de régions de moindre importance sociale telles que le décor en arrière-plan ou des objets [24,25], et leur balayage visuel est plus erratique, imprécis et désorganisé [26]. Klin et al [24] ont été les premiers à utiliser des stimuli dynamiques pour mesurer le balayage visuel effectué sur les visages par 15 adolescents avec autisme.…”
Section: Introductionunclassified
“…Grâce à ce dispositif, nous enregistrons le temps, le nombre et la durée moyenne des fixations visuelles que font les participants sur la scène visuelle. Nous adoptons ainsi les paramètres de mesure fréquemment utilisés dans les études oculométriques [21][22][23][24][25][26].…”
Section: Introductionunclassified
See 1 more Smart Citation